Experimental and theoretical study of ultra-hard AlMgB14-TiB2 composites: structure, hardness and self-lubricity - Nikitin, Pavel Yu; Zhukov, Ilya A.; Tkachev, Dmitriy; Abzaev, Yuri A.; Marchenko, Ekaterina S.; Vorozhtsov, Alexander B. (Materials)
It is known that the presence of oxygen phases in hard materials leads to an undesirable decrease in the mechanical properties. In materials based on AlMgB14, the main oxygen impurity is spinel MgAl2O4; it significantly reduces the hardness of AlMgB14 and its formation during sintering is inevitable. In this work, the ultra-hard spark plasma sintered (SPSed) AlMgB14-TiB2 composite material was fabricated from the AlMgB14-TiB2 precursor obtained by self-propagating high-temperature synthesis (SHS). Due to the high synthesis temperatures, the main oxygen phase in the obtained composite was Al4B2O9 instead of spinel MgAl2O4. It was found that the obtained composite has excellent mechanical properties. The maximum hardness of the sample is 44.1 GPa. The presence of oxygen in the form of the Al4B2O9 phase led to unexpected results: the friction coefficient of the obtained AlMgB14-TiB2 composite under dry conditions against the Al2O3 counter-specimen is approximately four times lower than the friction coefficient of pure ceramic AlMgB14 (0.18 against 0.7, respectively). Based on the observed results, it was found that the Al4B2O9 particles formed duringthe SHS are responsible for the low friction coefficient. The quantum chemical calculations showed that the elastic moduli of Al4B2O9 are significantly smaller than the elastic moduli of AlMgB14 and TiB2. Thus, during sliding, Al4B2O9 particles are squeezed out onto the composite surface, form the lubricating layer and reduce the friction coefficient.